1977
DOI: 10.1128/iai.15.2.410-416.1977
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of the eosinopenia of acute infection by passive transfer of a material obtained from inflammatory exudate

Abstract: Studies of the eosinopenic effect of acute inflammation were conducted in mice previously rendered eosinophilic with trichinosis. Exudate removed from a pneumococcal abscess contained material (eosinopenic factor [EF]) capable of causing eosinopenia of 4- to 24-h duration when injected intraperitoneally into eosinophilic mice. The material passed through a 0.45-micronm filter, but was retained by a dialysis membrane capable of retaining protein molecules of greater than approximately 30,000 molecular weight. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
2
4
0
2
Order By: Relevance
“…An enhanced migration of blood eosinophils to airway tissues can explain the marked eosinopenia during and immediately after the endurance challenge. Similar profound drops in the blood eosinophil count down to complete disappearance of eosinophils from the circulation have been described in acute inflammatory conditions, 17 acute physiologic stress, 4 and physical exercise. 18,19 In contrast to these findings, Gabriel et al 20 reported increased circulating eosinophils after short supramaximal exercise on a bicycle ergometer; this may be explained by mobilization of eosinophils due to the short duration of the physical effort.…”
Section: Discussionsupporting
confidence: 65%
“…An enhanced migration of blood eosinophils to airway tissues can explain the marked eosinopenia during and immediately after the endurance challenge. Similar profound drops in the blood eosinophil count down to complete disappearance of eosinophils from the circulation have been described in acute inflammatory conditions, 17 acute physiologic stress, 4 and physical exercise. 18,19 In contrast to these findings, Gabriel et al 20 reported increased circulating eosinophils after short supramaximal exercise on a bicycle ergometer; this may be explained by mobilization of eosinophils due to the short duration of the physical effort.…”
Section: Discussionsupporting
confidence: 65%
“…Persistent thrombocytopenia carried higher mortality in sepsis 42,43 , and in COVID-19 44,45 . Our analysis revealed a direct and unusually strong correlation between thrombocytopenia and eosinopenia in MIS-C. Eosinophils, on the other hand, as reviewed elsewhere 51 , have important antiviral properties, attributed to their granular proteins (e.g., eosinophil-derived neurotoxin, cationic protein) that display antiviral activities against single-stranded RNA viruses. Eosinophils can also support viral clearance 52 .…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, a sharply reduction in peripheral blood eosinophils does not only seem to be a result of adrenal mediation, because this was also observed in adrenalectomized rabbits 22 . Many researches proved that chemotactic factors such as complement 5a and brin fragments can mediate eosinophils migration to target organs or tissues, which may be one of the reason to drop the peripheral eosinophil count 24,25 . Ping J et al showed that eosinophil accumulation in the thrombus and decrease in peripheral blood in patients with acute coronary syndrome (ACS) 26 .…”
Section: Discussionmentioning
confidence: 99%